DUA DEKADE PENELITIAN GREEN ACCOUNTING DI INDONESIA: (SEBUAH SYSTEMATIK LITERATURE RIVIEW) - Mohamad Djasuli; Syifa Riyani Agustin; Khoirotul Amaliah; Dewi Kurnia Sari; Samania Samania (Politeknik Negeri Ambon, 2026)
Introduction: This study systematically maps and analyzes the development of green accounting research in Indonesia over the last two decades (2005–2025). It aims to identify significant trends, methodological patterns, thematic focuses, research gaps, and potential future directions. The topic has gained increasing academic interest in Indonesia, driven by growing demands for environmental responsibility and sustainable business practices. Methods: This qualitative study uses a Systematic Literature Review (SLR) approach to analyze 62 articles published in accredited national journals (Sinta 1 and 2) from 2005 to 2025. Articles were classified by research focus, methodology, and analytical techniques to reveal trends and gaps in the field.Results: These findings indicate a progressive movement in green accounting research, reflecting the increasing integration of environmental responsibility into business and academic discourse. However, the diversity of approaches and inconsistent results among these studies suggest that this field is still evolving and offers significant opportunities for further exploration. Conclusion and suggestion: Green accounting in Indonesia has made significant progress, but remains conceptually and practically diverse. Future research should extend beyond financial perspectives to include behavioral, governance, and sustainability dimensions. Increased awareness, regulatory support, and academic collaboration are essential for green accounting to become a transformative tool for sustainable development. Keywords: Green Accounting, Indonesia, Systematic Literature Review